A comparative study to assess the knowledge and beliefs regarding AIDS among higher secondary students in rural schools of South Kerala and South Tamil Nadu - Cyril, Jose P.; Stephenson, Baburaj; John, Joy; Alex, Anju Mirin; Paul, Sony S.; Sam, Merin Mariam; ., Teena; Mohan, Simi (International Journal of Contemporary Pediatrics, 2021)
Background: HIV continues to be a major global public health issue, having claimed 36.3 million lives so far. India has the third largest HIV epidemic in the world, with 2.1 million people living with HIV. Epidemiological data on AIDS suggests that in many cases, HIV infection was acquired during adolescence and lack of knowledge is one of the most important reasons. Hence, an ardent need was felt to assess the knowledge and beliefs of adolescents regarding AIDS. The main objective of this study was to assess the knowledge and beliefs regarding AIDS among higher secondary students of rural schools in South Kerala and in South Tamil Nadu. Methods: After getting ethical committee clearance, the study was conducted among higher secondary students of twelfth standard using a predesigned and validated self-administered questionnaire. An educational intervention regarding AIDS lasting for 30 min was given after the test. Data analysis was done using appropriate software. Results: The mean knowledge scores of students from Kerala (11.57) and Tamil Nadu (11.51) were almost same. Television, newspaper and teachers were the main source of information about AIDS. Beliefs like Whiteman’s disease can spread through mosquito bite, sharing vessels and giving shake hands/touching were highly prevalent in the study subjects. Conclusions: Proper emphasis should be given to teachers on mentoring adolescents and imparting them with the needed knowledge on HIV/AIDS to enable them to overcome this period of stress and storm.